In vitro studies of BMY-28142, a new broad-spectrum cephalosporin. - Bodey, G P (1985)
BMY-28142 was compared with other broad-spectrum antibiotics against gram-positive cocci and gram-negative bacilli. BMY-28142 was highly active against all gram-negative bacilli and especially against Enterobacter cloacae, Serratia marcescens, and Morganella morganii. Its in vitro activity suggests that BMY-28142 should prove to be useful for the treatment of gram-negative bacillary infections.